(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
European and national institutions increasingly rely on remote health care services to deal with main challenges arisen from demographic change and epidemiological transition in industrialized countries. The appearance of a new conception of care based on home-interventions and reduced access to emergence hospital is moreover encouraged by the severe economic constraints of the public health systems. In National context, although the recent approval of the first guidelines in the field, still remains some questions that need to be considered for the purpose of a coherent development of these services. Finally, it is addressed a suggestion arisen in the literature about a possible new dimension of health protection in the constitutional order, in the form of a “right to telehealth”.